2012
DOI: 10.1002/app.37680
|View full text |Cite
|
Sign up to set email alerts
|

Nanocomposites based on aromatic polyesters and organically modified clay

Abstract: Milled polybutylene terephthalate (PBT) and polytrimethylene terephthalate (PTT) were mixed with organically modified clay and extruded to prepare nanocomposites by melt intercalation. The modifier of the nanofiller belongs to the group of trialkylbenzylammonium cations. Manufacturing of the materials was carried out with a co-rotating twin-screw-extruder at 230°C and 240°C for PTT and PBT, respectively. A concentration of 3% of the inorganic filler component in the composites was aimed at. The influence of me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…PTT(SSP) prepared at 210°C was extruded with an OMC, modified with benzyldimethylstearylammonium cations, to manufacture composites with 3% of inorganic clay material. Based on the results of the first series of experiments,47 extrusion was performed at 200 and 400 rpm. The experimental contents of inorganic fillers in the composites, examined by pyrolysis, are presented in Table III.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…PTT(SSP) prepared at 210°C was extruded with an OMC, modified with benzyldimethylstearylammonium cations, to manufacture composites with 3% of inorganic clay material. Based on the results of the first series of experiments,47 extrusion was performed at 200 and 400 rpm. The experimental contents of inorganic fillers in the composites, examined by pyrolysis, are presented in Table III.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, polyester degradation has to be expected during extrusion, preferably at higher speeds of rotation 45. Manufacturing of aromatic polyesters like PET, PTT, and PBT in the presence of organically modified clays forces degradation of the polyesters 46, 47. Polymer degradation lowers polymer melt viscosity and works counterproductive with respect to the preparation of OMC‐nanocomposites by melt compounding.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is the most economically viable approach for continuous processes and large-scale uses (Acierno et al, 2011;Engelmann et al, 2013). It is the most economically viable approach for continuous processes and large-scale uses (Acierno et al, 2011;Engelmann et al, 2013).…”
Section: Melt Compounding and Injection Moldingmentioning
confidence: 99%
“…Engelmann et al (2013) suggested that the extrusion chamber required rinsing with nitrogen under reduced pressure to protect the polyester melts against oxidation and to remove volatile by-products. Manufacturing of the PBT/ clay nanocomposite was carried out with a co-rotating twin-screw-extruder at 240 °C.…”
Section: Melt Compounding and Injection Moldingmentioning
confidence: 99%